Contending issues in African development : advances, challenges, and the future - Iheduru, Obioma M. (Contributions in economics and economic history, 2001)
Annotation Taking a forward-looking approach, this book critically examines the issues and dynamics central to Africa's problematic development and situates these issues within the contents unique cultural, political, economic, and social milieu. Moving away from a simple litany of problems bedeviling Africa's economy, the book is the culmination of several scholars' efforts to identify specific causative factors. Each chapter delineates a specific issue, demonstrates the role it plays in overall development, and speculates on probable ways to meet the challenges it poses. The major conceptual and epistemological constructs considered include the tamed African State, social capacity, management of change, reconceptualized gender roles, and economic integration. Although the contributors' various approaches diverge and disagree, the epistemological variations contribute cumulatively to an understanding of the issues at the root of Africa's slow pace of development. While traversing the spectrum of issues that affect development, the book uniquely points out that the management of change is pivotal to fostering development. The authors' efforts provide a useful base for future research and help to chart a course of action leading to success in the 21st century.